1986
DOI: 10.1111/j.1528-1157.1986.tb03572.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Studies on Lamotrigine, A Novel Potential Antiepileptic Drug

Abstract: Lamotrigine (LTG), 3,5-diamino-6-(2,3-dichlorophenyl)-1,2,4-triazine, is a structurally novel anticonvulsant. The anticonvulsant profile of LTG following oral administration in two standard anticonvulsant tests, the maximal electroshock (MES) test in mice and rats and the pentylenetetrazol (PTZ) infusion test in mice, was studied in comparison with the known anticonvulsant drugs phenytoin (PHT), phenobarbitone, diazepam, carbamazepine (CBZ), sodium valproate, ethosuximide (ETH), and troxidone (TROX). ED50 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(77 citation statements)
references
References 6 publications
4
71
0
1
Order By: Relevance
“…LTG is active against tonic extension seizures in the MES test but is ineffective against scPTZ-induced clonus (40).…”
Section: Ltgmentioning
confidence: 99%
“…LTG is active against tonic extension seizures in the MES test but is ineffective against scPTZ-induced clonus (40).…”
Section: Ltgmentioning
confidence: 99%
“…It is available in several European countries and is awaiting FDA approval in the United States. Its preclinicd profile appears to be most similar to phenytoin (84). There have been several published safety and efficacy studies on lamotrigine in patients with epilepsy.…”
Section: Lamotriginementioning
confidence: 99%
“…In controlled clinical hids lamotrigine has demonstrated eflicacy in refractory patients with various seizures types (86) and refractory partial epilepsies (85,87). Chronic toxicity studies in rats and primates at doses of up to 20-125 mg/(kg day) have showed no toxic effects (84). The most frequently reported side-effects were diplopia, drowsiness, ataxia and headache (87).…”
Section: Lamotriginementioning
confidence: 99%
See 1 more Smart Citation
“…It is generally considered at present that the clinical success of a new antiarrhythmic agent would require a significant redress of the limitations of presently available therapy. During the course ofpharmacological studies at the Wellcome Research Laboratories, it was observed that certain phenyl diamino-1,2,4 triazines possessed anticonvulsant activity, a property attributable to the ability of these agents to modulate neuronal sodium transport (Miller et al, 1984;Leach et al, 1985). Preliminary evaluation demonstrated that some of these chemically novel triazines were also able to reduce, in a concentration-dependent fashion, the sodium-dependent rate of rise ofphase 0 of the cardiac action potential, an action ascribed as a class 1 antiarrhythmic action (Vaughan Williams, 1981).…”
Section: Introductionmentioning
confidence: 99%